2009
DOI: 10.1080/18146620903274704
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating the next generation of academics in South Africa

Abstract: The academic workplace is experiencing numerous changes in South Africa and around the world, including increasing managerialism, declining governmental funding and massifi cation of university systems. Global trends have impacted South Africa, and additional local contextual factors combine to create a situation in which the pool of prospective academics is limited, particularly with regard to individuals from diverse backgrounds, at the same time as vacancies for academic staff are expected to increase. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Although not set out to highlight gendered differences, Portnoi's (2009a;2009b) research on how new academics are shaped from South African postgraduate student data found that the barriers students faced in postgraduate studies include their feeling lost and isolated in their postgraduate studies; having difficulty relating postgraduate experiences to family and friends because of being a first-generation student; having difficult supervisory relationships; insufficient funding for postgraduate studies; feelings of racial inferiority, particularly among black women; experiencing undercurrents of institutionalised racism and culture; and a lack of guidance and support in becoming an academic. Of particular relevance to the current study are Portnoi's findings related to race.…”
Section: Numerical Representationmentioning
confidence: 99%
“…Although not set out to highlight gendered differences, Portnoi's (2009a;2009b) research on how new academics are shaped from South African postgraduate student data found that the barriers students faced in postgraduate studies include their feeling lost and isolated in their postgraduate studies; having difficulty relating postgraduate experiences to family and friends because of being a first-generation student; having difficult supervisory relationships; insufficient funding for postgraduate studies; feelings of racial inferiority, particularly among black women; experiencing undercurrents of institutionalised racism and culture; and a lack of guidance and support in becoming an academic. Of particular relevance to the current study are Portnoi's findings related to race.…”
Section: Numerical Representationmentioning
confidence: 99%
“…When combined with these changing emphases, the declining prestige of the academic profession (Altbach, 2000) and diminishing funding for HEIs in most parts of the world translates into adverse working conditions and low morale (Altbach, 2000; Bryson, 2004). These developments reflect the global march toward market-driven higher education in a time of unfavorable economic conditions, which further undermines the attractiveness of the academic profession (Altbach, 2000; Portnoi, 2009b). The arrival of the first Shanghai Jiaotong University HEI rankings in 2003 and the increasing use of such rankings by administrators in the higher education sector (Hazelkorn, 2008) are manifestations of the neoliberal influence in a challenging economic climate.…”
Section: Introductionmentioning
confidence: 99%